Are Women Liable for Blood-Money Payment?: An Attempt to Modify a Ḥanafī Rule - Tsafrir, Nurit (Hawwa, 2023)
Against the view that only men are liable for blood-money payment due for homicide, which goes back to pre-Islamic custom and was adopted by the Sharīʿa, by the fifth/eleventh century a new opinion appeared in Ḥanafī doctrine. According to this opinion, women who perpetrated a homicide were required to pay a share of the blood money due. Examining the context of this opinion in Ḥanafī literature, I suggest that it reflects the jurists’ tendency to put more weight on the Islamic principle of individual responsibility, regardless of gender. I propose that this opinion developed among Persian Ḥanafīs in eastern Iran, and follow the path through which it was incorporated into Ḥanafī standard law. Finally, I estimate the extent to which this opinion did influence Ḥanafī doctrine.